Effects of heat treatment on dynamic compressive properties and energy absorption characteristics of open-cell aluminum alloy foams - 曹晓卿 王志华 马宏伟 赵隆茂 杨桂通 (Transactions of Nonferrous Metals Society of China, 2006)
The effects of heat treatment on the dynamic compressive properties and energy absorption characteristics of open cell aluminum alloy foams （Al-Mg-Si alloy foam and Al-Cu-Mg alloy foam） produced by infiltrating process were studied. Two kinds of heat treatment were exploited： age-hardening and solution heat treating plus age-hardening （T6）. The split Hopkinson pressure bar （SHPB） was used for high strain rate compression test. The results show that both age-hardened and T6-strengthened foams exhibit improved compression strength and shortened plateau region compared with tnat of foams in as-fabricated state under high strain rate compression, and the energy absorption capacity is also influenced significantly by heat treatment. It is worthy to note that omitting the solution treating can also improve the strength and energy absorbed much.